DIRECTIONS FOR THE DEVELOPMENT OF ORGANIC FARMING IN SIBERIA ON THE INNOVATIVE AND INVESTMENT BASIS - Marina PETUKHOVA; Evgeniy RUDOY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The transition to highly productive and environmentally friendly agricultural farming is one of the priorities of the Strategy for Scientific and Technological Development of the Russian Federation. In the current conditions of sanctions policy, the need for a large-scale transfer of agriculture to organic farming increases. The purpose of the article is to develop methods and tools for the development of organic farming on an innovation and investment basis to ensure sustainable development of rural areas. The article presents the evolution of views and methodological approaches to studying the relationship between organic agriculture and sustainable development. The global trends in the development of the organic products market are studied, the dynamics of organic production in Russia are presented both in general and in the context of grain crops, legumes and vegetables. It has been empirically revealed that the bulk of the harvest of organic grain crops remains on the domestic market, and most of the leguminous crops are exported. The article examines global trends in the development of the organic products market. Methodological approaches and principles for the transition to the Organic 3.0 concept, aimed at intensifying the growth of organic product production, have been developed. Promising forms of organizing organic farming have been substantiated and conditions have been created for increasing the efficiency of organic production on an innovation-investment basis, taking into account regional specifics. The economic, social and environmental role of organic farming as a driver of sustainable development in Siberia is substantiated. Methods and tools have been developed to improve the state policy for the development of organic farming in rural areas of Siberia, including subsidies, subsidizing the purchase of certified planting materials, developing competency standards, and improving the regulatory framework. The practical significance of the results lies in the development of theoretical and methodological approaches and methodological tools for sustainable development of rural areas, based on the introduction of advanced organic farming technologies, as well as targeted mechanisms for stimulating organic production. organic farming, sustainable development, innovation and investment support,